ANALISIS EFISIENSI ENERGI LISTRIK PADA BOHLAM LAMPU MENGGUNAKAN SISTEM PANEL SURYA - Eti Elisa (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
The purpose of this study was to determine the efficiency of the use of solar panels applied to light bulbs. The purpose of this research is also to explain how the solar panels work and to find out the advantages of accuracy in their implementation. The method used is the journal review method regarding solar panels and electrical energy in light bulbs, using journals that have been recognized both nationally and internationally.